IMPLEMENTASI MANAJEMEN PROJEK PENGUATAN PROFIL PELAJAR PANCASILA DI SDIT PERMATA BUNDA DEMAK - Zulaichah Dwi Astuti; Maryanto; Ngurah Ayu Nyoman M (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This research aims to describe “The Implementation of Pancasila Student Profile Reinforcement Project Management at SDIT Permata Bunda Demak". Implementation includes: (1) planning; (2) implementation; (3) and evaluation. This research uses a qualitative approach with a multi-case study design. Data collection was carried out by interviews, observation and documentation. The research informants were the School Principal, District Elementary School Supervisor, Teachers, School Committee and Students. Data obtained from informants and research subjects were analyzed using qualitative data. Meanwhile, checking the validity of the data uses source triangulation. Based on the results of research on the management implementation of the Pancasila Student Profile Project, it can be concluded: (1) planning begins with work meetings with teachers, analyzing educational report cards, making KOSP, making P5 modules, preparing the Annual School Work Plan, and determining the P5 team as the person in charge, ( 3) implementation by determining the allocation of P5 time and activities according to the P5 module, (4) evaluation is carried out by the school principal periodically through evaluation meeting. Overall, the implementation of the project to strengthen Pancasila students at SDIT Permata Bunda has been carried out well. What needs to be improved further is teacher understanding regarding P5.